Long non-coding RNA FPFSC promotes immature porcine Sertoli cell growth through modulating the miR-326/EHMT2 axis - Dan Chu; Bin Chen; Bo Weng; Saina Yan; Yanfei Yin; Xiangwei Tang; Maoliang Ran (Journal of Integrative Agriculture, 2024)
Sertoli cells are indispensable for guaranteeing normal spermatogenesis and male fertility. Although a huge number of long non-coding RNAs (lncRNAs) are identified from developing porcine testicular tissues and have been predicted with crucial regulatory roles in spermatogenesis, their functions and regulatory mechanisms are still in infancy. Herein, we mainly explored the regulatory and functional roles of lncFPFSC in proliferation and apoptosis of immature porcine Sertoli cells. The results demonstrated that lncFPFSC was predominantly located in the cytoplasm of immature porcine Sertoli cells. lncFPFSC overexpression promoted cell cycle progression and cell proliferation, as well as inhibited cell apoptosis, whereas siRNA-induced lncFPFSC knockdown resulted in the opposite effects. Mechanistically, lncFPFSC acted as a sponge for miR-326. Overexpression of miR-326 inhibited cell proliferation and induced cell apoptosis, which further abolished the effects of lncFPFSC overexpression. The euchromatic histone-lysine N-methyltransferase 2 (EHMT2) gene was directly targeted by miR-326, and its mRNA and protein expressions were both negatively regulated by miR-326 in immature porcine Sertoli cells. Then, siRNA-induced EHMT2 knockdown resulted a similar effect of miR-326 inhibition. Collectively, lncFPFSC promoted proliferation and inhibited apoptosis in immature porcine Sertoli cells through modulating the miR-326/EHMT2 axis. This study expanded our understanding of non-coding RNAs in participating porcine spermatogenesis through deciding the fate of Sertoli cells, and the competing endogenous RNA (ceRNA) network, and provided new molecular markers to treat Sertoli cell disorder inducing male infertility.